Continuity between Stressful Experiences and Delusion Content in Adolescents with Psychotic Disorders – A Pilot Study - Catone, Gennaro; Pisano, Simone; Broome, Matthew; Lindau, Juliana Fortes; Pascotto, Antonio; Gritti, Antonella (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2016)
Background: Delusions are usually considered core symptoms of schizophrenia, but they are in fact associated with a wide range of psychiatric disorders. The content of a delusion is often related to stressful life experiences that preceded the delusion.Objective: The aim of this study is to detect whether there is a link—specifically, a thematic link—between past experiences and delusion content that connects the two events via thematic analogy.Method: The sample population evaluated for this study consisted of 16 consecutive patients with delusions between the ages of 9.9 and 16.5 years. All patients were experiencing their first psychotic episodes and were not taking any medications. Data were obtained from transcribed clinical sessions.Results: The data suggested the presence of a thematic link between previous experiences and the contents of delusions for 15 patients (93%). Humiliating events, including bullying, are more likely to be linked to persecutory delusions (p = .004). Conclusions: If a thematic link between past experiences and delusion content does exist, this may provide a means of greater psychotherapeutic understanding.